Subversion of immunoproteasome subunit expression in dengue virus serotype 2-infected HepG2 cells - Gan, C.S.; Lim, P.J.; Razif, M.F.M.; Yusof, R.; Othman, S. (Sociedade Brasileira de Medicina Tropical (SBMT), 2017)
Introduction: Infection with all serotypes of dengue virus (DV) results in augmented antigen presentation by MHC class I molecules. However, the upregulation of immunoproteasome subunits only results from infection with two serotypes. This study aims to elucidate changes in the expression of immunoproteasome subunits resulting from infection with DV, particularly DV serotype 2 (DV2). Methods: HepG2 cells were grown in various culture milieu. Total cellular RNA and proteins were extracted and quantified. Results: Results demonstrated sequestration of immunoproteasome subunits LMP2 and LMP7 in DV2-infected cells. Conclusions: This study provides insights into the mechanisms underlying immune evasion by DV.